Movie mooo / Sayang Zulida Zuikarnain and Normala Sulaiman - Zuikarnain, Sayang Zulida; Sulaiman, Normala (Academy of Language Studies, 2023)
Movies are the best source of entertainment in today’s lives. Numerous movie review websites just work to advertise the movie and aid viewers in choosing which movies to watch. There are not many websites that support the idea of learning English while advertising these movies. The purpose of this project is to spread enjoyment while picking up unfamiliar English words as well as promoting the movies with designed crochet bags that are themed with the movies reviewed. Using the questionnaire survey of 70 respondents aged 18 to 26 years old and above, it was found that 64.3% of the respondents could not understand English along with the example given. To help the audience to grasp the English language better, this Movie Mooo project uses Instagram, Canva and SCRL to publish short movie reviews with a passion for sharing quotes and uncommon English words. Further implications include the growth of other language components like speaking, writing, and listening.